2014
DOI: 10.1111/cea.12238
|View full text |Cite
|
Sign up to set email alerts
|

CD24hiCD27+ B cells from patients with allergic asthma have impaired regulatory activity in response to lipopolysaccharide

Abstract: Taken together, these data indicate that CD24(hi)CD27(+) B cells from allergic asthma patients produce less IL-10 in response to LPS leading to a weaker IL-10 induction in T cells in response to DerP1, which may play a role in allergic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 47 publications
(68 reference statements)
5
61
2
3
Order By: Relevance
“…Hi Breg frequencies have been observed in asthmatic patients not taking medication [10]. In our study, there were no differences in Breg subsets on comparing asthmatic and nonasthmatic patients, but our patients were all taking medication at recruitment.…”
Section: Cd38contrasting
confidence: 56%
See 1 more Smart Citation
“…Hi Breg frequencies have been observed in asthmatic patients not taking medication [10]. In our study, there were no differences in Breg subsets on comparing asthmatic and nonasthmatic patients, but our patients were all taking medication at recruitment.…”
Section: Cd38contrasting
confidence: 56%
“…Hi CD27 + Bregs have been observed in patients with asthma and/or allergic rhinitis [10,35], although increased CD24…”
Section: Decreased Frequencies Of Cd24mentioning
confidence: 99%
“…Thus, a relation between high proportions of neonatal CD5 + B cells and sensitization in children with allergic disease who are .3 y old may not be ruled out. Indeed, it was recently shown that sensitized adult subjects with allergic asthma had significantly higher proportions of circulating immature transitional B cells defined as CD24 hi CD38 hi compared with healthy individuals (32). It should be noted, however, that the absolute numbers of CD24 hi CD38 hi B cells did not differ between these two groups (32).…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study, B cells were attributed an important role in T H 2 responses and airway inflammation [9]. Impaired regulatory activity has also been reported for regulatory B cells (Bregs) in allergic asthma [10], and these cells are closely related to Tregs [11].…”
Section: Introductionmentioning
confidence: 98%